2009
DOI: 10.1007/s11192-008-2174-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing scientific research performance and impact with single indices

Abstract: We provide a comprehensive and critical review of the h-index and its most important modifications proposed in the literature, as well as of other similar indicators measuring research output and impact. Extensions of some of these indices are presented and illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 68 publications
(121 reference statements)
1
78
0
6
Order By: Relevance
“…The performance indicators of the researchers were also included in the analysis, such as the number of citations, the H-index and the M-index. [14][15][16][17][18] Statistical analysis The development of a database and the statistical analyses were conducted using the Statistical Package for Social Sciences (SPSS) software, version 18.0 for Windows. For the statistical analysis, regarding the grant holder categories, researchers were stratified into three groups: levels 1A and 1B, levels 1C and 1D and level 2.…”
Section: Variables Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance indicators of the researchers were also included in the analysis, such as the number of citations, the H-index and the M-index. [14][15][16][17][18] Statistical analysis The development of a database and the statistical analyses were conducted using the Statistical Package for Social Sciences (SPSS) software, version 18.0 for Windows. For the statistical analysis, regarding the grant holder categories, researchers were stratified into three groups: levels 1A and 1B, levels 1C and 1D and level 2.…”
Section: Variables Of Interestmentioning
confidence: 99%
“…16 The H-index consists of a single number that seeks to summarize two dimensions of academic performance: productivity (number of publications) and visibility (citations for those publications). 18,30,31 One point that has been emphasized about the H-index is that it counteracts both the excessive amount of publications with few citations as well as low productivity with many citations. 32 In our analysis, the median H-index for researchers in the field of Hematology/Oncology was 11, which was significantly higher for categories 1A and IB, with an H-index of 14.…”
Section: Impact Of the Scientific Productionmentioning
confidence: 99%
“…Although the h index appears better suited than IF for individual researchers, there are disadvantages (Panaretos & Malesios, 2009). It is bounded by the total number of publications and so disadvantages new researchers, however significant their work.…”
Section: Citation Measures For Researchersmentioning
confidence: 99%
“…These can also have their cons. A prominent critical review of the h-index can be found in a report by the joint Committee on Quantitative Assessment of Research (Adler, Ewing & Taylor 2008), while the extensive article by Panaretos & Malesios (2009) also critically reviews the h-index, and alternative single metrics (see also Moed &van Leeuwen 1996 andBornmann &Daniel 2007).…”
Section: Important Caveatsmentioning
confidence: 99%
“…Therefore, a number of objective, normalised metrics, rather than solely one, seems likely to persist. As argued by Panaretos & Malesios (2009), these should also be used in combination with other criteria such as memberships on editorial boards, awards, invitations or peer reviews when assessing the overall contributions of individual researchers.…”
Section: Total Citationsmentioning
confidence: 99%